Histone H4 lysine 16 acetylation regulates cellular lifespan - Dang, Weiwei; Steffen, Kristan K; Perry, Rocco; Dorsey, Jean A; Johnson, F. Brad; Shilatifard, Ali; Kaeberlein, Matt; Kennedy, Brian K; Berger, Shelley L (Nature (London), 2009)
Cells undergoing developmental processes are characterized by persistent non-genetic alterations in chromatin, termed epigenetic changes, represented by distinct patterns of DNA methylation and histone post-translational modifications. Sirtuins, a group of conserved NAD+-dependent deacetylases or ADP-ribosyltransferases, promote longevity in diverse organisms; however, their molecular mechanisms in ageing regulation remain poorly understood. Yeast Sir2, the first member of the family to be found, establishes and maintains chromatin silencing by removing histone H4 lysine 16 acetylation and bringing in other silencing proteins. Here we report an age-associated decrease in Sir2 protein abundance accompanied by an increase in H4 lysine 16 acetylation and loss of histones at specific subtelomeric regions in replicatively old yeast cells, which results in compromised transcriptional silencing at these loci. Antagonizing activities of Sir2 and Sas2, a histone acetyltransferase, regulate the replicative lifespan through histone H4 lysine 16 at subtelomeric regions. This pathway, distinct from existing ageing models for yeast, may represent an evolutionarily conserved function of sirtuins in regulation of replicative ageing by maintenance of intact telomeric chromatin.